Metaanálisis de los principales factores asociados a la fermentación cecal en cuyes (Cavia porcellus) en crecimiento - Feijoo Sanmartín, Nathaly Michelle (2024)
Cecal fermentation is a central metabolic function in guinea pigs, playing a fundamental role in their digestive physiology and general well-being. The present meta-analysis focuses on identifying the main factors affecting cecal fermentation in growing guinea pigs, based on data collected from 11 trials and 56 dietary treatments, which were entered into a database. A statistical correlation analysis was performed to study the linear relationships between cecal fermentation characteristics, chemical composition, and nutritional value of the diets. The analysis of the data collected in the database was carried out by statistical meta-analysis, using the MIXED procedure of SAS. A significant and positive relationship was found between the relative weight of the cecum and dietary NDF (P<0.05), as well as with dietary EE (P<0.05). However, cecal pH showed no significant relationship with dietary NDF (P>0.05), but with EE (P<0.05), indicating a direct influence of this component on digestive health (P<0.05). The composition of the diet, especially the EE content, significantly influences the cecal pH of guinea pigs, highlighting the importance of this factor in the digestive health of these animals. Además, tanto el contenido de FDN como el EE en la dieta ejercen una influencia determinante en el peso relativo del ciego en cuyes, lo que resalta la importancia crítica de una dieta adecuada para mantener una óptima salud digestiva en esta especie.